Positive almost periodicity on SICNNs incorporating mixed delays and D operator - Huang, Chuangxia; Liu, Bingwen; Yang, Hedi; Cao, Jinde (Nonlinear Analysis: Modelling and Control, 2022)
This article involves a kind of shunting inhibitory cellular neural networks incorporating D operator and mixed delays. First of all, we demonstrate that, under appropriate external input conditions, some positive solutions of the addressed system exist globally. Secondly, with the help of the differential inequality techniques and exploiting Lyapunov functional approach, some criteria are established to evidence the globally exponential stability on the positive almost periodic solutions. Eventually, a numerical case is provided to test and verify the correctness and reliability of the proposed findings.